Photodiodes: High‐Performance, Solution‐Processed Non‐polymeric Organic Photodiodes (Advanced Optical Materials 1/2015). Issue 1 (January 2015) - Kim, Il Ku; Pal, Bhola N.; Ullah, Mujeeb; Burn, Paul L.; Lo, Shih‐Chun; Meredith, Paul; Namdas, Ebinazar B.
<x xml:space="preserve">Abstract</x> On page 50, E. B. Namdas and co‐workers describe how key organic photodiode (OPD) device characteristics can be optimized and demonstrate high‐performance, solution‐processed, broadband OPDs based on a non‐polymeric organic semiconductor, including a near flat spectral response from 350 nm to 700 nm, a high responsivity (0.4 A/W), and a high detectivity (9.2×1012 Jones). These performance parameters are comparable to polymer‐ and inorganic silicon‐based photodiodes. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>